The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/ijopm-05-2016-0273
|View full text |Cite
|
Sign up to set email alerts
|

A morphological analysis of research literature on Lean Six Sigma for services

Abstract: Purpose The purpose of this paper is to review the existing literature on Lean Six Sigma (LSS) for services, construct a morphological analysis (MA) framework and identify research gaps to point to future research possibilities and priorities. Design/methodology/approach The MA framework is based on literature review of 175 papers published from 2003 to 2015, across 67 journals recognised by Scopus or ABS Academic Journal Quality Guide 2015. A three-phased methodology is used by the authors, with Phase1 feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 192 publications
(89 reference statements)
6
96
0
Order By: Relevance
“…Literature review is considered as one of the higher level of research evidence in other empirical testimonies as there is an element of analysis Copyright © Authors ISSN (Print): 2204-0595 ISSN (Online): 2203-1731 and synthesis in it [19]. Systematic reviews, which are different from ad-hoc reviews, has been recognized as a scientific activity and are being applied in other areas such as production economics too [20], [21], [22]. Further, a threestage protocol of gathering relevant literature, analysis and synthesizing data and drawing meaningful implications, as suggest by Transfield et al, [18] was used for the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature review is considered as one of the higher level of research evidence in other empirical testimonies as there is an element of analysis Copyright © Authors ISSN (Print): 2204-0595 ISSN (Online): 2203-1731 and synthesis in it [19]. Systematic reviews, which are different from ad-hoc reviews, has been recognized as a scientific activity and are being applied in other areas such as production economics too [20], [21], [22]. Further, a threestage protocol of gathering relevant literature, analysis and synthesizing data and drawing meaningful implications, as suggest by Transfield et al, [18] was used for the study.…”
Section: Methodsmentioning
confidence: 99%
“…The bibliographic analysis method was used. This method uses co-occurrence networks which, represents quantitative content based literature data [22]. In recent state of arts this method is identified as an effective method to represent literature data graphically by dividing it into clusters, to explore the recent trends.…”
Section: Data Analysis and Findings-mentioning
confidence: 99%
“…Machine learning techniques and big data analytics are applied in the healthcare fields for risk management, clinical decision support, chronic disease detection, and for precision medicine using genomic information [134]. The authors presented Lean Six Sigma application for improvements of patients' satisfaction, processing errors in healthcare payer firm using Six Sigma, and services of Lean Six Sigma for morphological analysis of research literature [135]- [137]. Table 9 depicts the research work reported using big data analytics in the fields of healthcare.…”
Section: F Rq5 What Are the Big Data Analytics In Healthcare?mentioning
confidence: 99%
“…Typically, some lean Six Sigma cases that have been reported in the literature are applied in service settings, including financial service, healthcare and local government. Although service sector covers about 36% of the body of literature concerning Six Sigma, this percentage is rising (Gamal Aboelmaged 2010) and Lean Six Sigma is emerging as a fundamental part of process improvement in service (Sunder, Ganesh, and Marathe 2018).…”
Section: Lean Six Sigma and Its Application In Servicementioning
confidence: 99%